How a Smart Environment Can Use Perception - Krumm, John; Shafer, Steve; Wilson, Andy (Workshop on Sensing and Perception for Ubiquitous Computing (part of UbiComp 2001), 2001)
Perception is a vital part of a smart environment, both as a way to sense the state of the space and a way to detect commands from its users. This paper catalogs different sorts of perception for smart environments using the EasyLiving project at Microsoft Research as the main example.